1998
DOI: 10.2307/3284737
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Observations on Cercariae and Metacercariae of Echinostoma trivolvis and Echinoparyphium sp.

Abstract: Comparative observations were made on cercariae of Echinoparyphium sp. from Physa gyrina in Charlie's pond, Stokes County, North Carolina and cercariae of Echinostoma trivolvis from Helisoma trivolvis in Northampton County, Pennsylvania. The cercaria of Echinoparyphium sp. has 43 collar spines, lacks penetration and paraesophageal glands, and has a conical tail without fin folds. The cercaria of E. trivolvis has 37 collar spines, penetration and paraesophageal glands, a finger-like process at the tip of the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Cercariae from each snail were morphologically identified as E. trivolvis (Fried et al. ), and were genetically identified as E. trivolvis lineage “a” (see below). Cercariae used in experiments were obtained by placing first intermediate infected snails under incandescent lights for up to 3 h (=maximum age of cercariae used).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cercariae from each snail were morphologically identified as E. trivolvis (Fried et al. ), and were genetically identified as E. trivolvis lineage “a” (see below). Cercariae used in experiments were obtained by placing first intermediate infected snails under incandescent lights for up to 3 h (=maximum age of cercariae used).…”
Section: Methodsmentioning
confidence: 99%
“…Echinostoma trivolvis cercariae for experiments were obtained from naturally infected first intermediate host H. trivolvis snails collected from a private pond in Montgomery County, Virginia. Cercariae from each snail were morphologically identified as E. trivolvis (Fried et al 1998), and were genetically identified as E. trivolvis lineage "a" (see below). Cercariae used in experiments were obtained by placing first intermediate infected snails under incandescent lights for up to 3 h (=maximum age of cercariae used).…”
Section: Basic Experimental Proceduresmentioning
confidence: 99%
“…Both molecular and morphological data support Echinostoma and Echinoparyphium as being distinct genera (Kostadinova et al 2003) . However, because they have relatively few recognizable features to separate them, especially as metacercariae, some workers believe that misidentification may be common (Sorensen et al 1997 ;Fried et al 1998) . Echinostoma revolutum has a more prevalent distribution in Europe, Asia, and Africa but has been confirmed in the midwestern USA by Sorensen et al (1997) using morphological traits and in Connecticut by Holland et al (2007) using molecular techniques.…”
Section: Overview Of Echinostomesmentioning
confidence: 99%
“…To help colleagues requesting aid with identification of these cercariae, Fried et al (1998) and Kanev et al (1998) described morphological characteristics and biological features of 43-collar-spined echinostomes in the genus Echinoparyphium from physid snails in the USA. This report is concerned with the identity of 45-collar-spined echinostomes of the Echinoparyphium recurvatum complex from physid snails in the USA.…”
Section: Introductionmentioning
confidence: 99%